2018
DOI: 10.1007/s12035-018-1435-8
|View full text |Cite
|
Sign up to set email alerts
|

Early Exposure to a High-Fat Diet Impacts on Hippocampal Plasticity: Implication of Microglia-Derived Exosome-like Extracellular Vesicles

Abstract: neuroinflamación como contexto patológico ………………………. Pág. 8. La autofagia y sus alteraciones …………………………………………. Pág. 9. Modelos animales de la enfermedad de Alzheimer …………………... Pág. 10. Tratamientos actuales y horizonte terapéutico ………………………... Pág.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 473 publications
(492 reference statements)
4
49
0
Order By: Relevance
“…Of note, innate and adaptive immune response, cytokine signaling, microglia function, activated microglia, and inflammatory signaling pathways had high undirected global significance (>5), suggesting that HFD feeding caused greater inflammatory response and microglial activation in the hippocampi of 5xFAD mice ( Figure 6 G). Our findings in HFD-fed 5xFAD mice were consistent with previous reports that HFD increases microglial activation in the hippocampus [ 51 , 52 , 53 ] which may promote synapse loss [ 51 ]. Collectively, our data showed that HFD combined with amyloid pathology is likely to increase stress on multiple pathways and cause detrimental effects on long-term synaptic plasticity, neuronal apoptosis, and neuroinflammation.…”
Section: Discussionsupporting
confidence: 93%
“…Of note, innate and adaptive immune response, cytokine signaling, microglia function, activated microglia, and inflammatory signaling pathways had high undirected global significance (>5), suggesting that HFD feeding caused greater inflammatory response and microglial activation in the hippocampi of 5xFAD mice ( Figure 6 G). Our findings in HFD-fed 5xFAD mice were consistent with previous reports that HFD increases microglial activation in the hippocampus [ 51 , 52 , 53 ] which may promote synapse loss [ 51 ]. Collectively, our data showed that HFD combined with amyloid pathology is likely to increase stress on multiple pathways and cause detrimental effects on long-term synaptic plasticity, neuronal apoptosis, and neuroinflammation.…”
Section: Discussionsupporting
confidence: 93%
“…While the mechanisms that mediate the biological effects of EVs on their cellular targets remain poorly known, it is clear that EVs are implicated in most, if not all, physiopathological processes, including signal transduction, cell growth, and differentiation, metabolic regulation, embryofetal development, organogenesis, tissue homeostasis and repair/regeneration, antigen presentation and immune response, ageing, pathogen-host interactions, carcinogenesis, tumor invasion/metastasis, cardiovascular dysfunction, etc. [9,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. The EV cargo, packaged within relatively stable membrane-bound structures, is sheltered from degradation by the extracellular enzymes present in biological fluids, and may therefore maintain biological stability over comparatively long periods of time [38].…”
Section: General Characteristics and Biological Significance Of Evsmentioning
confidence: 99%
“…The fact that Pik3r1 is abundantly expressed in mouse microglia [107] together with our RNAsequencing data prompted us to elucidate mouse microglial functions upon downregulation of Several studies have reported that HFD affects particularly microglial phenotype, function and/or inflammatory outcomes [3,20,98]. Trem2 has been shown to play a central role in AD and one of its functions is to act as a lipid-sensing receptor affecting microglial response [100].…”
Section: Discussionmentioning
confidence: 98%